2014
DOI: 10.1177/2048872614527008
|View full text |Cite
|
Sign up to set email alerts
|

Intracoronary thrombolysis in patients with ST-segment elevation myocardial infarction presenting with massive intraluminal thrombus and failed aspiration

Abstract: In STEMI patients with a large thrombus burden and failed manual aspiration, administration of low dose intracoronary thrombolysis is safe and reduces trhombus burden, as a result improving in epicardial flow and myocardial reperfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 23 publications
(34 reference statements)
1
27
0
Order By: Relevance
“…In our study, significant improvements in epicardial (cTFC) and myocardial (MBG) coronaryflow were found with the use of low dose intracoronary alteplase. Using different intracoronary thrombolytics, Sezer, et al [12] (using streptokinase) Boscarelli, et al, [13] (using alteplase and tenectplase) and Jayagopal and Sarjun-Basha, [14] (using tenectplase) found the same results. More physiologically, Sezer, et al [12] found that coronary flow reserve, index of microvascular resistance and Pressure derived collateral flow index were significantly lower in alteplase group.…”
Section: Acute Effects Of Intracoronary Alteplase Infusionmentioning
confidence: 81%
See 2 more Smart Citations
“…In our study, significant improvements in epicardial (cTFC) and myocardial (MBG) coronaryflow were found with the use of low dose intracoronary alteplase. Using different intracoronary thrombolytics, Sezer, et al [12] (using streptokinase) Boscarelli, et al, [13] (using alteplase and tenectplase) and Jayagopal and Sarjun-Basha, [14] (using tenectplase) found the same results. More physiologically, Sezer, et al [12] found that coronary flow reserve, index of microvascular resistance and Pressure derived collateral flow index were significantly lower in alteplase group.…”
Section: Acute Effects Of Intracoronary Alteplase Infusionmentioning
confidence: 81%
“…Export® catheter was used for manual thrombectomy as well as alteplase infusion for patients in alteplase group. The dose used was 0.3 mg/ kg as previously [13] which was infused just proximal to stent level over 5 minutes. The last angiogram was taken 15 minutes after completing the infusion.…”
Section: Primary Pcimentioning
confidence: 99%
See 1 more Smart Citation
“…Kelly et al [12] reported that intracoronary infusion of tenecteplase was safe and effective for coronary flow recovery in patients with myocardial infarction. More recently, Boscarelli et al [13] found that adjuvant intracoronary infusion of low dose tenecteplase and alteplase in STEMI significantly reduced the thrombi remaining after MAT and improved coronary blood flow. Several case reports of massive intracoronary thrombosis also described successful recovery of coronary blood flow after intracoronary thrombolysis using alteplase [14] and tenecteplase [15].…”
Section: Discussionmentioning
confidence: 99%
“…19 Similarly, intracoronary fibrinolysis with low-dose urokinase, tenecteplase or alteplase has also been described in cases of large thrombus burden and failed manual aspiration. 20,21 It is surprising that in the study by Luz et al, 12 while aspirin 300 mg and clopidogrel 600 mg were given to all patients before PCI, use of Gp IIb/IIIa inhibitors was low overall and similar in those with ineffective (38%) and effective TA (33.5%). In the Portuguese National Registry of Interventional Cardiology, of 3311 patients who underwent thrombectomy between January 2006 and December 2012 (performed in 46.1% of PCI procedures in 2012), use of Gp IIb/IIIa inhibitors was also low (36.9%) but significantly higher than in those undergoing primary angioplasty alone (18.9%, p=0.001).…”
mentioning
confidence: 99%